Quo Vadis Economic Law Policy in the Procurement of Goods and Services by the Government (Comparative Study of Indonesia and the Philippines) - Baiquni, Muhammad Iqbal; Rafikawati, Yulia Fajar (Recht Studiosum Law Review, 2022)
This paper discusses the legal development policy in the Government's Procurement of Goods and Services and to reveal the legal development sector in the regulation as well as a comparison of the Government's Procurement of Goods and Services policy between Indonesia and the Philippines. The method used in this paper is normative juridical with a statutory study approach (statue apporouch). The results of this study indicate that the direction of the government's procurement of goods and services policy is the achievement of the output and outcome of government agencies, economic improvement for both business actors and the community through economic equity and sustainable development, as well as comparisons related to government procurement of goods and services in Indonesia during the New Order era with integrity. The State Budget, however, is entering the decentralized Reform period and there are new regulations in the Government's Procurement of Goods and Services with the formation of an auction committee at each Office/Work Unit/Project Leader/Project Section. In the Philippines, it is formed in the Government Procurement Reform Act which is the basis for the regulation of Government Procurement of Goods and Services in the Philippines.